Resources, Technology and Sustainability An Analytical Perspective on Indian Agriculture - Sasmal, Joydeb (India Studies in Business and Economics, 2016)
This book uses sound theoretical frameworks and econometric techniques to rigorously analyze and explain the conditions of sustainable growth in agriculture. It further investigates how management of natural resources and technological advances can enhance productivity and ensure sustainable growth in agriculture. Optimal control theory, dynamic optimization problems and theory of risk and uncertainty are extensively used to create theoretical models for analyzing agricultural growth. The results demonstrate that crop diversification, rainwater harvesting and the use of organic fertilizers can ensure growth in agriculture from a dynamic perspective. Further, they show how excessive depletion of ground water, intensive farming and overuse of chemicals in connection with the adoption of modern technology in agriculture have placed tremendous strains on natural resources like land and water, and have called into question the sustainability of growth in the farming sector.